CANE AND BAMBOO CRAFT AND WOMEN’S SOCIAL EMPOWERMENT: EVIDENCE FROM RANCHI DISTRICT - Kumari, Anjali; Parashar, Pranay (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: The study investigates how participation in cane and bamboo craft activities influences different aspects of social empowerment among women artisans in the Ranchi district, focusing on household decision-making participation, freedom of movement, and reduction in domestic violence. Methodology: Primary data were collected from 440 women artisans through a structured questionnaire that included Likert-scale based questions. Ordinal logistic regression analysis was applied to evaluate how financial contribution and occupational involvement affect empowerment outcomes. Findings: The findings suggest that women who contribute financially to their households are more likely to participate in household decision-making. Occupational engagement has a statistically significant positive effect on freedom of movement, although with modest explanatory power. The analysis also revealed a significant association between women’s occupational engagement and a decline in experiences of domestic violence. Overall, engagement in cane and bamboo craft contributes positively to selected dimensions of social empowerment. Originality: This study provides empirical evidence on how participation in cane and bamboo craft influences different aspects of social empowerment among women artisans. It adds to the limited research available on the relationship between traditional handicraft employment and measurable social empowerment outcomes in a regional context.